Intermittent versus daily oral iron folic acid supplementation and pregnancy outcome in low- and middle-income countries: a systematic review and meta-analysis of experimental studies - Serawit Lakew Chillo; Endrias Markos Woldesemayat; Mesay Hailu Dangisso (Reproductive Health)
Abstract Trials were inconsistent while reporting findings on the benefits of the intermittent regimen. Recent conclusive evidence to show overall effect was limited. This review compared intermittent and daily iron folic acid supplementation (IFAS) on pregnancy outcomes. Protocol is registered at Prospero with registration number CRD42023409161. The major data sources searched were PubMed/Medline, Hinari, and Google Scholar. The process was reported using a PRISMA flow diagram. The included studies were trials with English language reports. The population was pregnant women. The intervention was an intermittent oral iron folic acid regimen, and the control was a daily regimen. The outcome measures were blood hemoglobin level, side effects, and medication adherence. The GRADE approach and Cochrane collaboration tool were used in the quality evaluation. The selected trials were narrated for basic characteristics and major findings. The standardized mean difference was used for continuous outcomes and the relative risk for binary outcomes. A sensitivity analysis was performed to report the robustness of the estimate. Twenty-two trials were selected for analysis. The quality of the evidence ranges from high to very low. Maternal blood hemoglobin levels were different between the intermittent and daily groups (mean difference (MD), − 0.24 g/dl; 95%CI, − 0.35, − 0.12). However, either early initiation or frequently intermittent regimen in the subgroup analysis showed no difference in hemoglobin levels. Intermittent regimens had lower gastric side effects (relative risk (RR), 0.27; 95%CI, 0.11, 0.69) and better medication adherences (relative risk (RR), 1.6; 95%CI, 1.34, 1.91). There was no clear evidence of a difference in anaemia incidence between the groups (relative risk (RR), 1.09; 95%CI, 0.77, 1.54). The overall level of hemoglobin in pregnancy was different between the groups. However, anaemia incidence was similar. The combined results suggest the intermittent regimen had better benefits in pregnancy than daily.